Setup to study the Compton scattering of entangled annihilation photons. Issue 1 (1st November 2022) - Strizhak, A; Abdurashitov, D; Baranov, A; Borisenko, D; Guber, F; Ivashkin, A; Morozov, S; Musin, S; Volkov, V
Abstract : The experimental setup to study the difference between Compton scattering of entangled and decoherent annihilation photons is discussed. The pairs of entangled gammas are born in electron-positron annihilation at rest. The polarization state of each photon in such a pair is not definite and represents the superposition of horizontal and vertical polarizations, while the relative polarizations of the photons are orthogonal. After interaction with the environment (for example, via the Compton scattering) the entangled pair of photons is broken and the pair becomes decoherent with determined polarizations of both gammas. Since the Compton scattering depends on the polarization of the initial photon, the scattering kinematics of entangled and decoherent photons might be quite different. At present, there is no experimental comparison of the Compton scattering kinematics for entangled and decoherent gammas.